Cardiogenic Shock - Bagaswoto, H. P.; Juzar, D. A.; Habib, F.; Bramantyo, Y. S.; Sanggula, P. N. P. P.; Widiastuti, A. Z. (Jurnal Kardiologi Indonesia, 2022)
Cardiogenic shock (CS) is the most common cause of death in hospitalized patients with acute myocardial infarction (AMI). The incidence and mortality of CS in hospitals is also high, although advanced therapy is widely used in CS patients. CS is a condition characterized by inadequate cardiac output due to primary cardiovascular diseases, leading to clinical and biochemical manifestations of insufficient tissue perfusion. CS complicates 5–10% of AMI. STEMI increases the risk of CS approximately twice as much as NSTEMI. In the last 10 years, in-hospital mortality due to CS that occurs in AMI has not changed, that is at 40-50%. The pathophysiology of CS shows several overlaps and can occur simultaneously, that is starting with a cardiac insult that reduces cardiac output, central hemodynamic changes, microcirculatory dysfunction, systemic inflammatory response syndrome, and multi-organ dysfunction. CS classification based on SCAI, divided into 5, that’s A(at risk), B(beginning CS), C(classic CS), D(deteriorating), and E(extremis). The key to managing CS is treating the patient as soon as possible, as each higher SCAI shock stage was associated with increased hospital mortality. All patients with suspected ACS-associated CS should have an early invasive strategy with appropriate revascularization. Vasoactive medicines have the potential to improve hemodynamics but at the expense of increased myocardial oxygen consumption and arrhythmogenic risk. Mechanical circulatory support (MCS) has insufficient data as the first-line device solution for CS patients. However, the use of durable MCS devices in a bridge-to-bridge strategy is becoming more prevalent and is supported by clinical recommendations. APACHE-III and SAPS-II, had the best mortality discrimination values to assess the outcome in CS patients.